The Design of Motorcycle’s Combustion Exhaust Gas Powered Tyre Pump - Riana Magdalena; Stefani Prima Dias Kristiana; Lukas Ambarita Saragih (Journal of ICT, Design, Engineering and Technological Science, 2018)
This research is motivated by observations and experiences of the researchers that a motorcyclist wants comfort while driving, but on a motorcycle, there can be many factors that cause problems. For example, experiencing a lack of air pressure on tyres (deflated) or a flat tyre becomes a serious problem when driving on a quiet road so that the driver feels disturbed. It is necessary to make a tool that can be used to pump tyres easily and efficiently. In making and designing tools, product specification design methods were used, ranging from task translation to detailed design. The Product Design Specification (PDS) method focuses on the criteria for being achieved in ideas and concepts. The value of pressure from the theoretical calculation is different from the calculation of the tool; the results of the theoretical calculation of the tool obtained air pressure of 38.8 Psi, while the tool testing can directly reach a pressure of 30 Psi. Although figure 30 Psi has been able to fill the front and rear tyres of a motorcycle, the difference in numbers is certainly caused by observable factors. With a variety of factors that affect the performance of the tool but still can meet enough criteria to be able to pump motorcycle tyres and also the design of this tool is made for use in emergency conditions, so that when a motorcycle experiences a flat tyre and the condition is not in the immediate vicinity with a tyre pump workshop, the tool can be used.